Structure, poetry, totality and fragment in Machu Picchu and La mano desasida (1954?-1980) by Martin Adam. Approaches to a new edition - Cavagnaro Farfán, Franco (2020)
Based on the affirmations of the poet Martín Adán in a journalistic article published in 1954, in one of his trips to Cusco, we will trace an opposition of the material and the structure that make up a change of verbal form and subject matter of the publication of the first fragment of La mano desasida in 1961, whose reference is the Machu Picchu Sanctuary. This allows us to reflect on the complexity between the limits of the Hispanic and the pre-Hispanic, and the processes of reuse of construction materials and reoccupation of space. Between knowledge and destruction that is a universal process in the evolution of time. We will thus assume the problematic of the totality and the fragment from its textual and archaeological correlates. This as a way of understanding the vastness of the file corresponding to the poet’s archive and the referent of the poem itself, Machu Picchu, its character as a complete or fragmentary real archaeological heritage.